Scaling up evidence-based approaches to tuberculosis screening in prisons. (April 2023) - Charalambous, Salome; Velen, Kavindhran; Rueda, Zulma; Croda, Julio; Herce, Michael E; Shenoi, Sheela V; Altice, Frederick L; Muyoyeta, Monde; Telisinghe, Lily; Grandjean, Louis; Keshavjee, Salmaan; Andrews, Jason R
Summary: People deprived of liberty have among the highest rates of tuberculosis globally. The incidence of tuberculosis is ten times greater than the incidence of tuberculosis in the general population. In 2021, WHO updated its guidance to strongly recommend systematic screening for tuberculosis in prisons and penitentiary systems. Which case-finding strategies should be adopted, and how to effectively implement these strategies in these settings, will be crucial questions facing ministries of health and justice. In this Viewpoint, we review the evidence base for tuberculosis screening and diagnostic strategies in prisons, highlighting promising approaches and knowledge gaps. Drawing upon past experiences of implementing active case-finding and care programmes in settings with a high tuberculosis burden, we discuss challenges and opportunities for improving the tuberculosis diagnosis and treatment cascade in these settings. We argue that improved transparency in reporting of tuberculosis notifications and outcomes in prisons and renewed focus and resourcing from WHO and other stakeholders will be crucial for building the commitment and investments needed from countries to address the continued crisis of tuberculosis in prisons.